Saúde mental e a contrução da masculinidade: perspectiva de adolescentes meninos - Gabriel, Isabela Martins (2024)
Female adolescents are more prone than male adolescents to have suicidal thoughts and suicide attempts. However, in Brazil, the suicide mortality rate is higher among men. The construction of masculinity seems to be part of the origin of this suffering, as well as impacting the ways in which these individuals are cared for. Objective: The aim of the study was to investigate the perspective of adolescent boys on mental health and its relationship with the construction of masculinity. Method: A qualitative approach research, based on Paulo Freire's critical pedagogical theory, using a participatory strategy for data construction - based on Culture Circles. Thirty-seven adolescent boys aged 13 to 15 from a state school participated in the study. Data collection included participant observation with field notes and the construction of artistic material facilitated by playful techniques. Data analysis was conducted through data triangulation. The research was approved by the Research Ethics Committee with Human Beings. Results: Findings indicated an optimistic perception of mental health, however, they presented triggering elements of psychic suffering, including the school environment, characterized by a dynamic of control and pressure, as well as the presence of bullying mainly linked to racism. The construction of masculinity was articulated with not expressing feelings, being signified by strength, aligned with the need to meet family expectations, mainly from the father or male figure. They reported perceiving a place of abandonment faced by individuals belonging to the LGBTQIA+ community. Furthermore, family and peers play an important role as a support network in the process of self-awareness, to identify and manage feelings. The context of social vulnerability can increase adolescents' exposure to risk situations. However, possible pathways were identified, such as empowerment through support networks and dialogical practices. The need for balance in internet use was pointed out, as well as sports recognized for their positive impacts on mental health and integration into the social construction process of masculinity. Final considerations: This study allowed an expanded look at mental health related to the construction of masculinity and allowed for thinking about nursing practice strategies, such as family empowerment and developing Nonviolent Communication in schools.